Obesity as a civilization threat of the XXI century. The Impact of obesity on individual functions of human organ systems - Martyna Warno; Adrian Maj (Nicolaus Copernicus University in Toruń, 2024)
Over time, obesity has become one of the most serious health problems facing contemporary society, posing a significant threat to public health. With the advancement of civilization and changes in people's lifestyles, obesity rates have increased worldwide, presenting us with challenges in terms of health and social well-being. Obesity, far exceeding a mere issue of physical appearance, carries serious health consequences for both individuals and entire societies. This publication aims to delve into the issue of obesity as a key factor affecting public health in the 21st century. The impact of obesity on individual organ systems will be analyzed, with particular emphasis on its adverse effects on the functioning of these systems.